2018
DOI: 10.1007/s11250-018-1553-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of meat quality characteristics and fatty acid composition of finished goat kids from indigenous and dairy breeds

Abstract: The aim of the study was to compare the certain carcass and meat quality traits and also fatty acid composition of goat kids from indigenous breeds (Gokceada and Hair Goat) and dairy breeds (Saanen and Maltese). A total 40 male kids from Saanen, Gokceada, Maltese and Hair Goat breeds were collected from commercial farms after weaning. Kids were finished for 56 days with grower concentrate and alfalfa hay in the sheepfold until slaughter. Higher mean values were found for Saanen kids in terms of slaughter weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 30 publications
0
17
2
1
Order By: Relevance
“…Values of approximately 30 N have been reported for very light suckling kids, such as capretto and cabrito at 1–2 d postmortem [18,19,43], in agreement with the results of our study. Other authors reported higher values than 30 N for kid meat [4,5,58] in meat aged from 1 d to 3 d. These values are also lower than those reported for other meats [59,60,61]. Additionally, these values are lower than the values of extremely tender beef [62,63].…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Values of approximately 30 N have been reported for very light suckling kids, such as capretto and cabrito at 1–2 d postmortem [18,19,43], in agreement with the results of our study. Other authors reported higher values than 30 N for kid meat [4,5,58] in meat aged from 1 d to 3 d. These values are also lower than those reported for other meats [59,60,61]. Additionally, these values are lower than the values of extremely tender beef [62,63].…”
Section: Discussionmentioning
confidence: 75%
“…Meat from goats is considered healthy because it is low in calories and fat [2]. However, Mediterranean goat farms are mainly focused on production of cheese and milk products because they have higher prices than cow milk [3,4,5]. When kid goats are reared with their dams, the availability of milk for cheese production is decreased, and the quality of milk may change.…”
Section: Introductionmentioning
confidence: 99%
“…De forma similar, pero menos clara, vemos que la carne con valores de a* menores de 6 es de animales de lactancia natural mientras que por encima de ese valor corresponde a animales criados en cualquiera de los dos sistemas. De acuerdo con esto, algunos autores encontraron que la carne de cabritos y corderos lechales alimentados con leche materna tuvo mayor tono, es decir, mayor índice de b* menor de a*, que la carne de animales alimentados con lactoreemplazantes (Osorio et al, 2008;De Palo et al, 2015;Yalcintan et al, 2018b). Estos autores justifican estas diferencias a diferencias en la cantidad de grasa intramuscular.…”
Section: Color Y Capacidad De Retención De Aguaunclassified
“…In recent years, with the increasing demand for goat milk and goat milk products such as ice cream and cheese, many dairy goat enterprises under intensive or semi-intensive conditions have been established. In these farms, Saanen and Maltese breeds, which are generally known for their high milk yield, are preferred (Ekiz et al, 2010;Yalcintan et al, 2018). Milk constitutes the main income item in dairy goat farms, and the sale of male kids is also an important subsidiary income.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, low-weight carcasses are also obtained in the extensive production system carried out with indigenous breeds, and the meat production potential of the kids is not sufficiently utilized (Ekiz et al, 2010;Özcan et al, 2010;. In both production models made with indigenous breeds under the extensive system and with dairy breeds under the semi-intensive or intensive systems, fattening of kids in the intensive fattening programme after weaning can be considered as an effective method to increase the production of kid meat (Yalcintan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%